The pedagogy of memorial sites - KOŃCZYK, LUIZA (Journal of Education Culture and Society, 2020)
Memorial site pedagogy is a term describing the practice and theory of historico-poli-tical education in museums in former nazi concentration camps. It combines gaining and deepening historical knowledge on the topic of World War II with self-development and shaping socially desirable attitudes, through usage of non-formal educational methods. Pedagogy of memorial sites aims at, among other things, learning tolerance and respect for diversity and shaping refl ective and active members of society. It offers an answer to the needs of contemporary European societies in the area of strengthening democratic attitudes.